Molecular imaging of human thrombus with novel abciximab immunobubbles and ultrasound - Alonso, Angelika; Della Martina, Alberto; Stroick, Mark Gregor; Fatar, Marc; Griebe, Martin; Pochon, Sibylle; Schneider, Michel; Hennerici, Michael G.; Allémann, Eric; Meairs, Stephen (Stroke, 2007)
BACKGROUND AND PURPOSE: Molecular imaging of therapeutic interventions with targeted agents that simultaneously carry drugs or genes for local delivery is appealing. We investigated the ability of a novel microbubble carrier (immunobubble) for abciximab, a glycoprotein IIb/IIIa receptor inhibitor, for ultrasonographic molecular imaging of human clots. - METHODS: Human thrombi were incubated with immunobubbles conjugated with abciximab. Control clots were incubated in either saline or with immunobubbles conjugated with nonspecific antibody. We evaluated immunobubble suspensions with variable concentrations of encapsulated gas and measured mean acoustic intensity of the incubated clots. In vivo molecular imaging of human thrombi with abciximab immunobubbles was evaluated in a rat model of carotid artery occlusion. - RESULTS: Mean acoustic intensity was significantly higher for abciximab immunobubbles as compared with control immunobubbles under all conditions tested with maximum difference in intensity at a gas volume of 0.2 microL (P=0.0013 for mechanical index 0.05, P=0.0001 for mechanical index 0.7). Binding of abciximab immunobubbles to clots in vitro led to enhanced echogenicity dependent on bubble concentration. In vivo ultrasonic detectability of carotid thrombi was significantly higher for clots targeted with abciximab immunobubbles (P<0.05). Quantification of in vivo contrast enhancement displayed a highly significant increment for abciximab immunobubble-targeted clots compared with nonspecific immunobubble-targeted clots (P<0.0001) and to native clots (P<0.0001). - CONCLUSIONS: This study demonstrates the feasibility of using a therapeutic agent for selective targeting in vascular imaging. Abciximab immunobubbles improve visualization of human clots both in vitro and in an in vivo model of acute arterial thrombotic occlusion.